The effect of the dispersion medium nature on the suspensive cooligomerization process of C9 fraction - Orobchuk, Oksana; Romankiv, Iryna; Polishchuk, Bohdan; Subtelnyy, Roman (Видавництво Львівської політехніки, 2013)
Processing by-products of ethylene production – liquid pyrolysis products is actual problem nowadays. Industrial methods of initiated cooligomerization of unsaturated hydrocarbon fraction C9 have several disadvantages such as high temperature, duration of reaction, high performance color of oligomer. To eliminate the difficulties carrying out of the process of cooligomerization in suspension is proposed to use precipitant as a dispersion medium for cooligomerization with components [fraction C9] [dispersion medium] is suggested. A number of precipitants is as the dispersion medium ethanol, hexane and water is selected. Influence of dispersion medium on the processs is investigated. The dependence of the yield and chemical characteristics of oligomer from nature of precipitant is shown. The optimal correlation of the components of the suspension is defined.
Keywords: Suspension cooligomerization; hydrocarbons fraction; initiator; oligomer; ethanol; hexane